Optimization of exogenous CeO2 nanoparticles on Pak choi (Brassica rapa L. var. chinensis) to alleviate arsenic stress - Rohina Tabassam; Shoaib Ahmad; Adiba Khan Sehrish; Azeem Ahmad; Sarah Owdah Alomrani; Abdul Ghafoor; Tahira Akram; Muhammad Ali Alshehri; Sumaira Noor; Shafaqat Ali; Shafaqat Ali (Frontiers in Plant Science)
Arsenic (As) is a regulated hazardous substance that persists in the environment, causing issues related to environmental health, agriculture, and food safety. Cerium oxide nanoparticles (CeO2 NPs) are emerging sustainable solutions for alleviating heavy metal stress. However, their effectiveness and optimization for foliar application in reducing As stress, especially in Pak choi, has not been reported yet. Hence, this study aims to examine the effects of foliar application of CeO2 NPs (75,000,000, 150,000,000, and 300,000,000 ng/L) on the growth, nutrient availability, and antioxidant enzymatic activities of Pak choi plants under As stress. The findings showed that foliar application of 75,000,000 ng/L CeO2 NPs significantly increased shoot length (77.32%), root length (80.98%), and number of leaves (80.23%) as compared to control without NPs. The lowest dose of CeO2 NPs (75,000,000 ng/L) increased antioxidant enzyme activities such as peroxidase (86.10%), superoxide dismutase (81.48%), and catalase (52.07%), while significantly reducing malondialdehyde (44.02%), hydrogen peroxide (34.20%), and electrolyte leakage (43.53%). Furthermore, foliar application of 75,000,000 ng/L CeO2 NPs significantly increased the content of zinc (81.02%), copper (56.99%), iron (88.04%), manganese (68.37%), magnesium (76.83%), calcium (61.16%), and potassium (84.91%) in leaves when compared to control without NPs. The same trend was observed for shoot and root nutrient concentrations. Most importantly, 75,000,000 ng/L CeO2 NPs foliar application significantly reduced shoot As (45.11%) and root As (20.89%) concentration compared to control, providing a reassuring indication of their potential to reduce As concentration in plants. Our study’s findings are of utmost importance as they indicate that lower concentrations of foliar-applied CeO2 NPs can be more effective in enhancing crop nutrition and reducing heavy metals than higher concentrations. This article is intended to present critical issues of As contamination in agricultural soils, which imposes substantial risks to crop productivity and food security.